TINJAUN HUKUM POSITIF DI INDONESIA TENTANG PERJANJIAN PRA NIKAH - Surawardi, Surawardi; Zarkani, Muhammad (Program Studi Hukum Keluarga Islam STAI Al-Falah Banjarbaru, 2025)
Abstract A prenuptial agreement is an agreement between prospective husband and wife that regulates property, rights and obligations during marriage. A prenuptial agreement is a new problem that is not included in the pillars and requirements for a valid marriage in Islam. Therefore, this problem needs to be studied from a mashlahah mursalah perspective. The purpose of this study is to determine the provisions of prenuptial agreements in Indonesia and to study prenuptial agreements using a mashlahah mursalah perspective. What are the provisions of prenuptial agreements in Indonesia? And What is the law on prenuptial agreements from a mashlahah mursalah perspective? This research is classified as a normative literature research type, with qualitative data type, with a normative juridical approach. The technique of collecting legal materials is by means of documentary studies, then the legal materials are selected, interpreted, and understood to be analyzed with mashlahah mursalah. The results of the study show that prenuptial agreements in Indonesia are regulated in the Civil Code articles 139-154, the Marriage Law article 29, the KHI articles 45-52, and PMK-RI No. 69/PUU-XIII/2015. This agreement is made based on mutual agreement, made before or during the marriage. The content does not violate law, religion, norms and decency. As well as providing benefits for couples, such as legal certainty, managing assets, and avoiding losses as a means of preventing conflict. This is in line with the principle of mashlahah murlah, namely real, general benefit, bringing benefits and avoiding harm.Keywords: Mashlahah Mursalah, Prenuptial AgreementAbstrak: Perjanjian pra nikah adalah suatu kesepakatan antara calon pasangan suami istri yang mengatur harta benda, hak dan kewajiban selama pernikahan. Perjanjian pra nikah merupakan permasalahan baru yang bukan termasuk rukun dan syarat sahnya pernikahan dalam Islam. Maka persoalan ini perlu dikaji dengan perspektif mashlahah mursalah.Tujuan penelitian ini untuk mengetahui ketentuan perjanjian pra nikah di Indonesia dan mengkaji perjanjian pra nikah dengan menggunakan perspektif mashlahah mursalah, bagaimana ketentuan perjanjian pra nikah di IndonesiaPenelitian ini tergolong dalam jenis penelitian normatif kepustakaan, dengan jenis data kualitatif, dengan pendekatan yuridis normatif. Tehnik pengumpulan bahan hukum dengan cara studi dokumenter, kemudian bahan hukum diseleksi, diinterpretasikan, dan dipahami untuk dianalisis dengan mashlahah mursalah.Hasil penelitian menunjukan, perjanjian pra nikah di Indonesia diatur dalam KUH Perdata pasal 139-154, Undang-Undang Perkawinan pasal 29, KHI pasal 45-52, dan PMK-RI No. 69/PUU-XIII/2015. Perjanjian ini dibuat berdasarkan kesepakatan bersama, dibuat sebelum dilangsungkan atau selama dalam ikatan perkawinan. Isinya tidak melanggar hukum, agama, norma, dan kesusilaan. Serta memberikan kemaslahatan bagi pasangan, seperti kepastian hukum, pengaturan harta, dan menolak kemudaratan sebagai pencegahan konflik. Ini sejalan dengan prinsip mashlahah mursalah yaitu kemaslahatan yang nyata, bersifat umum, serta mendatangkan manfaat dan menolak mudarat. Kata Kunci : Perjanjian Pra Nikah, Mashlahah Mursalah